An Analysis of Policy Solutions to Mitigate the Impact of Greenhouse Gas Emissions and Increase Public Awareness and Participation - Mak Chanmony (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This research paper analyzes potential policy responses to the problem of greenhouse gas emissions and the need to raise public knowledge and engagement in the fight against climate change. The analysis is geared toward filling in gaps and suggesting ways to better the policy frameworks and efforts already in place. According to the results, more attention should be paid to adaptation policies, more emphasis should be placed on behavioral change, and international collaboration should be stepped up. The thesis offers a holistic strategy for combating climate change by engaging decision-makers, influencers, and the general public. This study highlights the need for continuous policy review and adjustment to maximize efficiency and fairness. Policymakers can create policies that are more comprehensive, equitable, and effective in reducing the effects of greenhouse gas emissions and raising public awareness and participation in climate action by addressing the highlighted gaps and areas for improvement. The climate catastrophe is an emergency that requires immediate action from policymakers. This thesis's analysis lays a groundwork for future studies and policymaking in this field. Together, we can protect future families from the worst impacts of climate change by creating policies that actually work.